KAJIAN DURASI PERENDAMAN AUXIN NATURAL PADA PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L) - puspitorini, palupi; Kurniastuti, Tri (Universitas Islam Balitar, 2019)
The aims of this study is to determine the soaking time of the seeds with natural auxin which is appropriate for the growth and production of shallots (Allium ascalonicum L). The study was arranged in a randomized treatment group 7 treatment and repeated 4x. The treatment was soaking time of shallot seeds (D). There are 28 field trial units. Treatment consisted of D0 = without soaking, D1 = soaking 2 hours, D2 = soaking 4 hours, D3 = soaking 6 hours, D4 = soaking 8 hours, D5 = soaking 10 hours, D6 = soaking 12 hours. The variables observed were shoot length, shallot / plant weight, tuber diameter. The results of the study showed that the 3 variables observed showed the best results in D3 treatment (soaking for 6 minutes) in natural coconut water. The best treatment is D3, which is a tuber weight value of 41.01 grams per plant with a tuber diameter of 2.01 cm.